Predictors of preference for cognitive-behavioral therapy (CBT) and yoga interventions among older adults. (June 2021) - Brenes, Gretchen A.; Munger Clary, Heidi M.; Miller, Michael E.; Divers, Jasmin; Anderson, Andrea; Hargis, Gena; Danhauer, Suzanne C.
Abstract: The purpose of this study was to examine factors that influence a person's choice of cognitive-behavioral therapy (CBT) or yoga, the stability of these preferences, and the impact of preference on engagement and process measures. We conducted a randomized preference trial of CBT and yoga in 500 adults ≥60 years with symptoms of worry. Participants reported their intervention preference, strength of preference, and factors impacting preference. Engagement in the intervention (session completion and dropout rates) was assessed. Process measures included satisfaction with the intervention, therapeutic alliance, and intervention expectancy. Neither intervention preference (48% and 52% chose CBT and yoga, respectively) nor strength of preference differed significantly between the two preference trial groups. Intervention expectancies at baseline among those in the preference trial were approximately 4.5 units (40-point scale) higher for their preferred intervention (p < .0001 within each group). A principal component analysis of factors influencing preference identified three constructs. Using logistic regression, components focused on attitudes about CBT or yoga were predictive of ultimate preference (odds ratio = 11.5, 95% C.I.6.3–21.0 per 1SD difference in component 1 for choosing CBT; odds ratio = 7.8, 95% CI4.3–13.9 per 1SD difference in component 2 for choosing yoga). There were no significant differences between the randomized and preference trials on intervention adherence, completion of assessments, intervention satisfaction, or working alliance. Receiving a preferred treatment had no significant effects on intervention outcomes through participant engagement or process measures. When options are limited, providers may have confidence in offering the most readily available non-pharmacological treatments.